MINERALOGICAL AND CHEMICAL EVOLUTION OF THE ERNEST HENRY FE OXIDE–CU–AU ORE SYSTEM, CLONCURRY DISTRICT, NORTHWEST QUEENSLAND, AUSTRALIA - Mark G.; Oliver N.H.S.; Williams P.J. (My University, 2006)
The Ernest Henry Cu–Au deposit was formed within a zoned, post-peak metamorphic hydrothermal system that overprinted metamorphosed dacite, andesite and diorite (ca 1740–1660 Ma). The Ernest Henry hydrothermal system was formed by two cycles of sodic and potassic alteration where biotite–magnetite alteration produced in the first cycle formed ca 1514±24 Ma, whereas paragenetically later Na–Ca veining formed ca 1529 +11/−8 Ma. These new U–Pbtitanite age dates support textural evidence for incursion of hydrothermal fluids after the metamorphic peak, and overlap with earlier estimates for the timing of Cu–Au mineralization (ca 1540–1500 Ma). A distal to proximal potassic alteration zone correlates with a large (up to 1.5 km) K–Fe–Mn–Ba enriched alteration zone that overprints earlier sodic alteration. Mass balance analysis indicates that K–Fe–Mn–Ba alteration—largely produced during pre-ore biotite- and magnetite-rich alteration—is associated with K–Rb–Cl–Ba–Fe–Mn and As enrichment and Na, Ca and Sr depletion. The aforementioned chemical exchange almost precisely counterbalances the mass changes associated with regional Na–Ca alteration. This initial transition from sodic to potassic alteration may have been formed during the evolution of a single fluid that evolved via alkali exchange during progressive fluid-rock interaction. Cu–Au ore, dominated by co-precipitated magnetite, minor specular hematite, and chalcopyrite as breccia matrix, forms a pipe-like body at the core of a proximal alteration zone dominated by K-feldspar alteration. Both the core and K-feldspar alteration overprint Na–Ca alteration and biotite–magnetite (K–Fe) alteration. Ore was associated with the concentration of a diverse range of elements (e.g. Cu, Au, Fe, Mo, U, Sb, W, Sn, Bi, Ag, F, REE, K, S, As, Co, Ba and Ca). Mineralization also involved the deposition of significant barite, K(–Ba)–feldspar, calcite, fluorite and complexly zoned pyrite. The complexly zoned pyrite and variable K–(Ba)–feldspar versus barite associations are interpreted to indicate fluctuating sulphur and/or barium supply. Together with the alteration zonation geochemistry and overprinting criteria, these data are interpreted to indicate that Cu–Au mineralization occurred as a result of fluid mixing during dilation and brecciation, in the location of the most intense initial potassic alteration. A link between early alteration (Na–Ca and K–Fe) and the later K-feldspathization and the Cu–Au ore is possible. However, the ore-related enrichments in particular elements (especially Ba, Mn, As, Mo, Ag, U, Sb and Bi) are so extreme compared with earlier alteration that another fluid, possibly magmatic in origin, contributed the diverse element suite geochemically independently of the earlier stages. Structural focussing of successive stages produced the distinctive alteration zoning, providing a basis both for exploration for similar deposits, and for an understanding of ore genesis.
Keywords: PROTEROZOIC; HYDROTHERMAL FLUIDS; ALTERATION ZONING; SODIC; POTASSIC; EXPLORATION VECTORS; Precambrian::Proterozoic; Докембрий::Протерозой